Water quality improvement method based on palygorskite and purple sand composite material appliance

Through the porous honeycomb structure and backwash cleaning technology of the saglis and purple clay composite equipment, the problem of traditional water purification technology being difficult to remove heavy metals and organic pollutants is solved, and efficient water purification and long-life equipment is achieved, reducing maintenance costs.

CN119114007AInactive Publication Date: 2024-12-13HUAIAN QINGLIANGANG CERAMIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411319486.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional water quality purification technology is difficult to effectively remove heavy metal ions and organic pollutants, and the water purifier filter element has a short service life, which increases the economic burden.

Method used

The slurry and purple clay are mixed in a ratio of 1:1 to 3:1. The particle size is less than 10 microns through wet grinding. The binder is added and the porous honeycomb structure is formed by high-pressure forming. The slurry is used to absorb heavy metal ions and purple clay. Filter the organic pollutants and clean by backflushing, with a waterproof corrosion-resistant layer on the surface.

Benefits of technology

It has achieved comprehensive purification of water quality, extended the service life of the appliance, improved adsorption and filtration efficiency, inhibited microbial growth, and reduced maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114007A_ABST
    Figure CN119114007A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water quality purification, and discloses a water quality improvement method based on a palygorskite and purple sand composite material utensil, which comprises the following steps: (a) uniformly mixing palygorskite and purple sand according to a weight ratio of 1: 1-3: 1, and enabling the particle size of the mixture to be less than 10 microns in a wet grinding manner, uniform mixing is ensured, and a larger specific surface area can be provided; (b) adding a proper amount of binder into the mixture; (c) performing compression molding on the uniformly stirred composite material through a high-pressure molding machine to form an appliance with a porous honeycomb structure; by matching the palygorskite and the purple sand and utilizing different adsorption characteristics of the palygorskite and the purple sand, heavy metal ions in water can be effectively removed, comprehensive purification of water quality is achieved, a proper amount of binder is added, the structural stability and mechanical strength of the composite material are enhanced, and through the porous honeycomb structure, smooth water flow is guaranteed, and meanwhile the water quality is improved. And the effective contact area of water and the composite material is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water purification, and in particular to a water quality improvement method based on a palygorskite and purple sand composite material appliance. Background Art

[0002] With the acceleration of industrialization and the advancement of urbanization, water pollution is becoming increasingly serious, and the safety of drinking water has become one of the focuses of people's attention. Although traditional water purification technologies, such as sedimentation, filtration, disinfection and other methods, can remove suspended matter and some pollutants in water to a certain extent, they still have shortcomings for some difficult-to-remove heavy metal ions and organic pollutants. In addition, traditional water purifier filters often have a short service life and are frequently replaced, which increases the economic burden on users.

[0003] At present, most of the common water purification devices on the market use a single material or a simple combination of materials as the filter medium. These materials either have limited adsorption capacity or low filtration accuracy, which makes it difficult to meet the high standards of water quality required by modern people. Especially for water containing a variety of complex pollutants, a single purification method is often difficult to achieve the ideal purification effect. Therefore, a water quality improvement method based on a composite material appliance of palygorskite and purple sand is proposed. Summary of the invention

[0004] The object of the present invention is to provide a method for improving water quality based on a composite material appliance of palygorskite and purple sand to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for improving water quality based on a composite material appliance of palygorskite and purple sand, comprising: A working platform is placed on the ground, and the top of the working platform is provided with the following steps: (a) uniformly mixing palygorskite and purple sand in a weight ratio of 1:1 to 3:1, and wet grinding the mixture so that the particle size is less than 10 microns to ensure uniform mixing and provide a larger specific surface area; (b) adding an appropriate amount of a binder to the mixture, wherein the binder accounts for 1% to 5% of the total weight of the mixture, and fully stirring the mixture by a stirrer to uniformly distribute the binder, so as to enhance the structural stability and mechanical strength of the composite material; (c) pressing the uniformly stirred composite material through a high pressure molding machine to form a device having a porous honeycomb structure, wherein the pore size of the honeycomb is between 0.1 mm and 1 mm, and the porosity is greater than 50%, so as to ensure smooth water flow and maximize the effective contact area between water and the composite material; (d) drying the formed device by low temperature drying at a temperature not exceeding 80°C for at least 24 hours to prevent structural changes of the composite material due to excessive temperature; (e) placing the dried device in a water tank to be treated, and allowing water to continuously pass through the device through a water circulation system, during which the palygorskite in the composite material is used to adsorb heavy metal ions in the water, and the purple sand plays a role in further filtering and adsorbing organic pollutants, thereby jointly improving water quality; (f) regularly removing impurities attached to the apparatus by backwashing to restore its adsorption capacity and filtration efficiency and ensure the long-term effective operation of the apparatus.

[0006] Preferably, the weight ratio of palygorskite to purple sand is 2:1 to achieve optimal adsorption and filtration effects.

[0007] Preferably, the porous honeycomb structure is arranged in a hexagonal shape to ensure maximum water flow channel density and minimum water flow resistance.

[0008] Preferably, the surface of the device is provided with one or more layers of microporous membranes, wherein the pore size of the microporous membranes is less than 0.1 mm, so as to further intercept fine suspended particles in the water.

[0009] Preferably, the method further comprises step (e), coating a waterproof and corrosion-resistant protective layer on the surface of the device to extend the service life of the device.

[0010] Preferably, an antibacterial agent is added during the preparation of the composite material in step (c) to inhibit the growth of microorganisms in water.

[0011] Preferably, the antibacterial agent is silver ion or copper ion, and the added amount is 0.5% to 2% of the total weight of the composite material.

[0012] Preferably, a certain proportion of activated carbon is added to the composite material to enhance the adsorption capacity of organic pollutants.

[0013] Preferably, the added amount of the activated carbon is 0.5%-2% of the total weight of the composite material to achieve the best adsorption effect.

[0014] Preferably, the surface of the device is coated with a waterproof and anti-corrosion coating to extend the service life of the device, and the waterproof and anti-corrosion coating is a polytetrafluoroethylene coating to provide excellent chemical stability and wear resistance.

[0015] The present invention has at least the following beneficial effects: (1) This scheme uses the different adsorption characteristics of palygorskite and purple sand to effectively remove heavy metal ions in water and further filter out organic pollutants, thereby achieving comprehensive water purification. Adding an appropriate amount of binder enhances the structural stability and mechanical strength of the composite material, making the device less prone to damage during use and extending its service life. The porous honeycomb structure ensures smooth water flow while increasing the effective contact area between water and the composite material, further improving the purification efficiency.

[0016] (2) This solution increases the specific surface area of ​​the material by controlling the particle size of the mixture to less than 10 microns, thereby improving the adsorption efficiency and filtration effect, making the purification process more thorough.

[0017] (3) This scheme adds activated carbon and antibacterial agents to the composite material, which not only improves the adsorption capacity of organic pollutants, but also inhibits the growth of microorganisms and reduces the possibility of secondary pollution.

[0018] (4) This solution coats the surface of the device with a waterproof and corrosion-resistant protective layer, such as a polytetrafluoroethylene coating, which greatly improves the durability of the device and reduces the user's maintenance cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0020] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] See also Figure 1 The present invention provides a technical solution: a method for improving water quality based on a composite material appliance of palygorskite and purple sand, comprising the following steps: (a) uniformly mixing palygorskite and purple sand in a weight ratio of 1:1 to 3:1, and wet grinding the mixture so that the particle size is less than 10 microns to ensure uniform mixing and provide a larger specific surface area; (b) adding an appropriate amount of a binder to the mixture, wherein the binder accounts for 1% to 5% of the total weight of the mixture, and fully stirring the mixture by a stirrer to uniformly distribute the binder, so as to enhance the structural stability and mechanical strength of the composite material; (c) pressing the uniformly stirred composite material through a high pressure molding machine to form a device having a porous honeycomb structure, wherein the pore size of the honeycomb is between 0.1 mm and 1 mm, and the porosity is greater than 50%, so as to ensure smooth water flow and maximize the effective contact area between water and the composite material; The porous honeycomb structure is arranged in a hexagonal pattern to ensure maximum water flow channel density and minimum water flow resistance.

[0023] (d) drying the formed device by low temperature drying at a temperature not exceeding 80°C for at least 24 hours to prevent structural changes of the composite material due to excessive temperature; (e) placing the dried device in a water tank to be treated, and allowing water to continuously pass through the device through a water circulation system, during which the palygorskite in the composite material is used to adsorb heavy metal ions in the water, and the purple sand plays a role in further filtering and adsorbing organic pollutants, thereby jointly improving water quality; (f) regularly removing impurities attached to the apparatus by backwashing to restore its adsorption capacity and filtration efficiency and ensure the long-term effective operation of the apparatus.

[0024] In some embodiments, the weight ratio of palygorskite to purple sand is preferably 2:1 to achieve optimal adsorption and filtration effects. The surface of the device is provided with one or more microporous membranes, the pore size of which is less than 0.1 mm, to further intercept fine suspended particles in the water.

[0025] The method further comprises step (e), coating a waterproof and corrosion-resistant protective layer on the surface of the device to extend the service life of the device.

[0026] In the preparation process of the composite material in step (c), an antibacterial agent is also added to inhibit the growth of microorganisms in water. The antibacterial agent is silver ions or copper ions, and the addition amount is 0.5% to 2% of the total weight of the composite material.

[0027] A certain proportion of activated carbon is added to the composite material to enhance the adsorption capacity of organic pollutants. The amount of activated carbon added is 0.5%-2% of the total weight of the composite material to achieve the best adsorption effect.

[0028] The surface of the device is coated with a waterproof and anti-corrosion coating to extend the service life of the device. The waterproof and anti-corrosion coating is a polytetrafluoroethylene coating to provide excellent chemical stability and wear resistance.

[0029] It should be noted that an appropriate ratio of palygorskite and purple sand is selected, preferably a ratio of 2:1 (i.e., one part of purple sand for every two parts of palygorskite), and they are uniformly mixed at a weight ratio of 1:1 to 3:1. Then, the mixture is placed in a wet grinding device for grinding until the particle size of the mixture is reduced to less than 10 microns. This ensures that the mixture is evenly distributed and has a large specific surface area, which is beneficial to the subsequent adsorption process.

[0030] In the above ground mixture, a binder is added at a ratio of 1% to 5% of the total weight. The selection of the binder should take into account the performance of the final product, such as adsorption capacity and filtration efficiency. After adding the binder, use a mixer to stir it thoroughly to ensure that the binder is evenly distributed in the mixture, thereby improving the structural stability and mechanical strength of the composite material.

[0031] The mixed composite material is placed in a high-pressure molding machine for compression molding. The molded device should be designed to have a porous honeycomb structure, in which the pore size range is set between 0.1mm and 1mm, the porosity exceeds 50%, and the honeycomb structure is preferably arranged in a hexagonal shape to facilitate water flow while increasing the effective contact area between water and the composite material. In addition, a certain proportion (0.5%-2%) of activated carbon and / or silver ion or copper ion antibacterial agents can be added to the composite material to enhance the adsorption capacity of organic pollutants and inhibit the growth of microorganisms.

[0032] The formed device needs to be dried by low-temperature drying for at least 24 hours at a temperature not exceeding 80°C. This step is to prevent high temperature from causing changes in the structure of the composite material, thereby affecting its performance.

[0033] The dried equipment is placed in the water tank to be treated, and water is continuously passed through the equipment through the water circulation system. During this process, palygorskite will adsorb heavy metal ions in the water, while purple sand will further filter and adsorb organic pollutants in the water. In order to ensure the long-term and effective operation of the equipment, impurities attached to it are regularly removed through backwashing and cleaning to restore its adsorption capacity and filtration efficiency.

[0034] In order to further improve the effect of improving water quality, one or more microporous membranes (pore size less than 0.1mm) can be set on the surface of the device to intercept fine suspended particles in the water. In addition, a waterproof and corrosion-resistant protective layer (such as polytetrafluoroethylene coating) can also be coated on the surface of the device to extend the service life of the device.

[0035] Working principle: Palygorskite is a natural mineral. Due to its unique layered structure and high cation exchange capacity, it can effectively adsorb heavy metal ions in water, such as lead, cadmium, mercury, etc., thereby reducing the concentration of these harmful substances. Zisha is a natural material with high porosity. It can not only act as a physical filtration medium to remove larger particulate matter in water, but also further adsorb organic pollutants in water, such as pesticides and detergent residues, through its internal microporous structure. The particle size of the mixture is controlled to less than 10 microns by wet grinding, which helps to increase the specific surface area of ​​the material and thus improve the adsorption efficiency. The increase in specific surface area means that the unit mass of material can contact more pollutants, improving the purification effect. The addition of 1%-5% of the binder allows the composite material to maintain good adsorption performance while also having high structural stability and mechanical strength, and is not easy to break or wear during long-term use. The composite material is pressed into an appliance with a porous honeycomb structure, which not only ensures the unimpeded flow of water, but also maximizes the effective contact area between water and the composite material due to its porosity greater than 50%, further improving the adsorption and filtration efficiency. Regularly removing impurities attached to the equipment through backwash cleaning can not only restore its adsorption capacity and filtration efficiency, but also prevent blockage and ensure the normal operation of the system.

[0036] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for improving water quality based on a composite material of palygorskite and purple sand, characterized in that: The following steps are involved: (a) uniformly mixing palygorskite and purple sand in a weight ratio of 1:1 to 3:1, and wet grinding the mixture so that the particle size is less than 10 microns to ensure uniform mixing and provide a larger specific surface area; (b) adding an appropriate amount of a binder to the mixture, wherein the binder accounts for 1% to 5% of the total weight of the mixture, and stirring the mixture thoroughly with a stirrer to ensure that the binder is evenly distributed; (c) pressing the uniformly stirred composite material through a high pressure molding machine to form a device having a porous honeycomb structure, wherein the pore size of the honeycomb is between 0.1 mm and 1 mm; (d) drying the formed device by low temperature drying at a temperature not exceeding 80°C for at least 24 hours; (e) placing the dried utensil in a water tank to be treated, and allowing water to continuously pass through the utensil through a water circulation system, during which the palygorskite in the composite material is used to adsorb heavy metal ions in the water, and the purple sand plays a role in further filtering and adsorbing organic pollutants; (f) Regularly remove impurities adhering to the apparatus by backwashing to restore its adsorption capacity and filtration efficiency.

2. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 1, characterized in that: The weight ratio of palygorskite to purple sand is preferably 2:

1.

3. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 1, characterized in that: The porous honeycomb structure is arranged in a hexagonal shape.

4. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 1, characterized in that: The surface of the device is provided with one or more microporous membranes, and the pore size of the microporous membranes is less than 0.1 mm.

5. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 1, characterized in that: The method further comprises step (e), coating a waterproof and corrosion-resistant protective layer on the surface of the device to extend the service life of the device.

6. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 1, characterized in that: During the preparation of the composite material in step (c), an antimicrobial agent is also added to inhibit the growth of microorganisms in water.

7. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 6, characterized in that: The antibacterial agent is silver ion or copper ion, and the added amount is 0.5% to 2% of the total weight of the composite material.

8. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 1, characterized in that: A certain proportion of activated carbon is added to the composite material to enhance the adsorption capacity of organic pollutants.

9. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 8, characterized in that: The added amount of the activated carbon is 0.5%-2% of the total weight of the composite material to achieve the best adsorption effect.

10. The method for improving water quality based on a composite material of palygorskite and purple sand according to claim 1, characterized in that: The surface of the device is coated with a waterproof and anti-corrosion coating to extend the service life of the device. The waterproof and anti-corrosion coating is a polytetrafluoroethylene coating.